Marc Dierikx, Anthony Fokker. Een vervlogen leven - van Loo, Erwin (BMGN - Low Countries Historical Review, 2015)
Marc Dierikx, Anthony Fokker. Een vervlogen leven (Amsterdam: Boom, 2014, 416 pp., isbn 978 90 8953 284 8).